2002
DOI: 10.1103/physrevb.65.125408
|View full text |Cite
|
Sign up to set email alerts
|

Imaging mechanism of piezoresponse force microscopy of ferroelectric surfaces

Abstract: In order to determine the origin of image contrast in piezoresponse force microscopy (PFM), analytical descriptions of the complex interactions between a small tip and ferroelectric surface are derived for several sets of limiting conditions. Image charge calculations are used to determine potential and field distributions at the tip-surface junction between a spherical tip and an anisotropic dielectric half plane. Methods of Hertzian mechanics are used to calculate the response amplitude in the electrostatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
355
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(360 citation statements)
references
References 62 publications
5
355
0
Order By: Relevance
“…Using piezoresponse force microscopy (PFM) [20][21][22] and P-E hysteresis loop measurements, we found that multidomain states that incorporate charged domain walls do not exhibit bulk polarization switching, whereas lamella domain structures consisting of neutral domain walls do. This result is further corroborated by real-space observations of pinned charged domain walls under an electric field.…”
Section: Textmentioning
confidence: 99%
“…Using piezoresponse force microscopy (PFM) [20][21][22] and P-E hysteresis loop measurements, we found that multidomain states that incorporate charged domain walls do not exhibit bulk polarization switching, whereas lamella domain structures consisting of neutral domain walls do. This result is further corroborated by real-space observations of pinned charged domain walls under an electric field.…”
Section: Textmentioning
confidence: 99%
“…28 Here, we extend this analysis to the frequency dependence of the dominant contrast. Frequency dependence of the VPFM signal including electromechanical and local and non-local electrostatic contributions is given in Section II.…”
Section: Iv2 Frequency Regimes In Pfmmentioning
confidence: 99%
“…In the linear model, the lateral spring constant of the tip-surface junction is 28 Similarly to electromechanical contributions, dynamic effects in the high-frequency regime will strongly affect the magnitude of local and distributed electrostatic responses.…”
mentioning
confidence: 99%
“…A now thriving community for PFM research and development exists, pushing the technique forward and establishing good practice amongst the global research community [85][86][87][88][89]. However, PFM is unlikely to be the only probe needed for the characterisation of nanoscale ferroelectrics.…”
Section: Characterisation Of Nanoscale Ferroelectricsmentioning
confidence: 99%